(untitled) (Journal of Digital System Development, 2025)
Philately, commonly known as stamp collecting, is a globally embraced and culturally rich hobby with historical significance. This study delves into the transformative influence of StampAlbumCollect, a web-based personalised stamp album application, on the traditional practice of stamp collecting. Departing from conventional reliance on physical albums, collectors now grapple with opportunities and challenges introduced by Information and Communication Technology (ICT) in the digital era. StampAlbumCollect, a user-friendly platform harnessing ICT advancements, redefines how collectors engage with stamp collections, offering a seamless experience regardless of location. Beyond organisational advantages, StampAlbumCollect becomes a dynamic hub for knowledge sharing among collectors, acting as a catalyst for community-building in this time-honoured hobby. The study follows an iterative model, collaborating with stamp collectors and analysing existing stamp collection websites to develop StampAlbumCollect’s requirements meticulously. This iterative approach ensures adaptability, responsiveness, and continuous improvement based on user feedback, maintaining dynamic alignment with user needs. Feedback from respondents on StampAlbumCollect overwhelmingly reflects positive perceptions concerning practical experience, usability, usefulness, ease of learning, and overall satisfaction. The application receives notable acclaim for its ease of use, user-friendliness, and efficiency. While a few instances of neutrality are present, the predominant sentiment is positive, affirming StampAlbumCollect’s success and providing insights for potential enhancements. Future enhancements for StampAlbumCollect may encompass expanded customisation tools, advanced data analytics for user behaviour insights, and the creation of a dedicated mobile application. These advancements further enhance user satisfaction, ensuring StampAlbumCollect’s ongoing success and valuable contribution to the evolving landscape of digital stamp collecting.